Two-photon absorption-based delivery of nitric oxide from ruthenium nitrosyl complexes. Issue 39 (28th September 2022) - Lacroix, Pascal G.; Malfant, Isabelle; Labra-Vázquez, Pablo; Fárfan, Norberto; Ramos-Ortiz, Gabriel
Abstract : Two-photon absorption (TPA) processes are used to induce nitric oxide (NO) delivery from ruthenium nitrosyl complexes. Abstract : Since the discovery of the numerous physiological roles exhibited by nitric oxide (NO), ruthenium nitrosyl (RuNO) complexes have been regarded as one of the most promising NO donors, stable, well tolerated by the body and capable of releasing NO locally and quantitatively, under light irradiation. This release can be achieved by two-photon absorption (TPA) processes, which allow the irradiation to be performed in the near infrared domain, where light has its maximum depth of penetration in biological tissues. This review provides a short introduction on the biological properties of NO, on RuNO complexes with photo-releasing capabilities, and on the origin of TPA properties in molecules. Then, the RuNO complexes with TPA capabilities are thoroughly discussed either as monometallic or polymetallic species.